Enablers In Implementing Micro Sourcing For The Low Income Group In Malaysia - Arshad, Noor Habibah; Syed Aris, Syaripah Ruzaini; Salleh, Siti Salwa; Janom, Norjansalika; Mastuki, Nor’azam (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Improved access to ICTs and related services through micro sourcing initiatives has created new opportunities for enterprises with direct involvement of the poor to access information and other input. Micro sourcing provides benefit around the strengthening of social and intellectual capital through enhancement of skills, increased self-confidence and empowerment. The positive impacts of micro sourcing on micro worker are crucial in sustaining the uplifting poor income household through the micro sourcing initiative.Â This paper will determine the enablers through SWOT and Gap analysis. The SWOT analysis is to evaluate many aspects and competitors for the enablers of micro sourcing, while Gap analysis is targeted towards the fine tuning of the process. A SWOT and GAP analysis workshop was held to gather information from stakeholders. The findings from the SWOT analysis will identify potential pitfalls and allow us to take action to avoid them. Meanwhile, the GAP analysis may allow us to define the source of the problem and targeted towards fine tuning the micro sourcing process.